2013
DOI: 10.1088/0957-4484/24/31/315701
|View full text |Cite|
|
Sign up to set email alerts
|

Phosphorylated silica nanotubes: preparation and characterization

Abstract: Recently, the strategy of doping inorganic particles into polymer membranes to modify them has been studied intensively. However, these inorganic particles have a disadvantage without being in good compatibility with the polymers. To enhance the compatibility between inorganic particles and polymers, phosphorylated silica nanotubes (PSNTs) with specific high ratios of length to diameter are prepared. Silica nanotubes (SNTs) are prepared through the hydrolysis of tetraethyl orthosilicate in a mixture of aqueous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…The weight loss of Si-imP at 320°C to 700°C is far greater than that of SiO 2 , which is mainly caused by thermal decomposition of aminopropyl and other organic components. 35 The above results indicate that Si-imP was successfully prepared.…”
Section: Resultsmentioning
confidence: 66%
“…The weight loss of Si-imP at 320°C to 700°C is far greater than that of SiO 2 , which is mainly caused by thermal decomposition of aminopropyl and other organic components. 35 The above results indicate that Si-imP was successfully prepared.…”
Section: Resultsmentioning
confidence: 66%
“…Considering the above problems, Zhang et al synthesized phosphorylated silica nanotubes (PSNTs) as a better filling material to modify PVDF membranes [13], which took the advantages of silica nanotubes (SNTs) with hollow structures, high specific surface areas, high ratio of length to diameter, biocompatibility and good anti-compaction strength etc [14]. The results showed that in the length direction of PSNTs, there are many accessible active sites to be compatible with the polymer membrane along the direction of polymer chains; in the diameter direction of PSNTs, there is a unique circular wall with nanometer thickness, which can function as a new energy dissipation approach to resist the outer impact forces.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to their low density, large void space, and specific surface area, HMMs are promising in various applications, such as adsorption and storage, confined catalysis, optical devices, enzyme immobilization, etc. [18][19][20][21] For example, an amphiphilic block copolymer 22 and a mixture of aqueous ammonia and tartaric acid 23 were used for softtemplating hollow mesoporous silica nanoparticles with tunable shell thickness and pore size and phosphorylated silica nano-tubes with high length-to-diameter ratios, respectively. 4,[6][7][8][9][10][11][12][13][14][15][16][17] A template-directed synthesis strategy is an ideal tool to fabricate hollow materials because the resultant physical dimensions can be precisely controlled and monodisperse samples can be harvested in large quantity.…”
Section: Introductionmentioning
confidence: 99%
“…In general, there are two main synthetic routes to produce HMMs, soft-and hard-templating. [18][19][20][21] For example, an amphiphilic block copolymer 22 and a mixture of aqueous ammonia and tartaric acid 23 were used for softtemplating hollow mesoporous silica nanoparticles with tunable shell thickness and pore size and phosphorylated silica nano-tubes with high length-to-diameter ratios, respectively. Silicate hollow nanotubes were synthesized via hard-templating by replicating carbon nanotubes via a sol-gel process with heat treatment.…”
Section: Introductionmentioning
confidence: 99%